KEPATUHAN SYARIAH DAN IMPLIKASINYA TERHADAP RISIKO FRAUD DI BANK UMUM SYARIAH INDONESIA (PERIODE 2017-2023) - Rizki Dwi Anggraini (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
Islamic Commercial Banks operate based on Sharia principles, yet they remain at risk of experiencing fraud. Fraud cases occurring between 2017 and 2023 highlight the need for mitigation efforts, one of which is through Sharia compliance and the implementation of Islamic Corporate Governance (ICG). This study aims to analyze the influence of Sharia compliance, measured through several ratios such as Islamic Income Ratio (IIR), Profit Sharing Ratio (PSR), Islamic Investment Ratio (IsIVR), and Zakat Performance Ratio (ZPR), on fraud, with ICG as a control variable. The research data is obtained from annual reports and GCG of Sharia banks registered with the OJK, using a sample of eight banks selected through purposive sampling. The analysis is conducted using panel data regression with Eviews 12. The results show that IsIVR has a positive impact on fraud, while IIR, PSR, and ZPR do not have a significant effect. Simultaneously, all independent variables have a positive and significant effect on fraud in Islamic Commercial Banks.